Usefulness of outreach clinics on active case detection of leprosy in a high endemic area in Sri Lanka - Kasunee Kalubowila; Chandana Gajanayaka; Chaminda Hapudeniya; Indira Kahawita; Lakmal Jayarathna; Sankha Vithanage; Manuja Thilakarathna; Jayalath Gunathilaka; Sounthararajan Anujan (College of Community Physicians of Sri Lanka, 2023)
Though Sri Lanka reports low endemicity and a lesser number of cases detected annually, leprosy patients below 14 years of age are rising. Therefore, active case finding is essential. A skin clinic was conducted in the District Hospital (DH), Lunawa of Colombo District where higher numbers of cases had been reported in the past. The people were alerted on the clinic through public health staff to identify new cases. Out of the 54 persons who attended the clinic, one was clinically diagnosed as having multibacillary leprosy and another subsequently detected among the five suspected patients who were referred for skin biopsy, giving a yield of active case finding of 0.37 per 10 000 persons screened (95% CI: 0.45, 1.26). This high yield of the disease indicates that active case finding is a possible strategy for high endemic areas, which could be enhanced with a combination of outreach programs like household surveys or awareness on leprosy at institutions like schools.